Understanding physical activity from a cultural-contextual lens - Rio, Carielle Joy; Saligan, Leorey N. (Frontiers in Public Health, 2023)
This paper aims to emphasize the need to acknowledge unique cultural and contextual meanings of physical activity, to improve health outcomes in different communities. Leininger's Sunrise Model was used as the theoretical base to understand the complex cultural and contextual factors that influence physical activity.Beliefs and practices surrounding physical activity are influenced by a variety of cultural and contextual factors. Providing culturally relevant contexts to the meaning of physical activity allows opportunities for improving policies or programs that would engage individuals and communities in physical activity in culturally meaningful ways.Incorporating cultural and contextual factors is critical to promote physical activity, especially in minority and vulnerable communities.